Effect of six degrees of freedom knee kinematics on ligament length and moment arm in an intact knee model - Ozada, Neriman (Ios Press, 2015)
BACKGROUND: Biomechanics studies can help improve athletic performance. However, the biomechanics of knee joint ligament length changes and moment arms over six degrees of freedom (DOF) have yet to be established. OBJECTIVE: To construct a knee model to investigate the length and moment arm changes of the anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), medial collateral ligament (MCL), and lateral collateral ligament (LCL). METHOD: Six DOF joint modeling and analysis were performed using specialized modeling software. RESULTS: The length of all ligaments varied with tibiofemoral flexion angle, contributed to joint motion, and restrained the joint in different positions. The ACL, MCL, and LCL lengths decreased, the PCL increased, the posterior tibial translation increased, the MCL moment arm increased, and the LCL moment arm decreased between 0 degrees and 90 degrees. The primary ligament restraints were the PCL (0 degrees to 30 degrees), MCL (30 degrees to 60 degrees), and PCL (60 degrees to 90 degrees). CONCLUSION: The restraining function of each ligament during motion can be modeled based on changes in ligament lengths during tibial translations and rotations during flexion. Understanding the correlations between ligament lengths and moment arm changes over a wide range of motion will help improve our understanding of joint kinematics and may be useful for the diagnosis and treatment of sports injury.
Keywords: Biomechanics; anterior cruciate ligament; posterior cruciate ligament; medial collateral ligament; lateral collateral ligament